Effectiveness of ferric sodium edentate supplementation in children with lead poisoning - Praevilia Salendu; Nurhayati Masloman; Sarah M. Warouw (Paediatrica Indonesiana, 2017)
Background Lead is a harmful toxin that affects human health worldwide, especially in children. Lead poisoning remains a global problem both in developed and developing countries. The Centers for Disease Control and Prevention (CDC) recommends nutritional intervention with iron supplementation to efficiently control high lead levels. Iron supplementation in the form of sodium ferric ethylene-diaminetera-acetic acid/ ferric sodium edentate (NaFeEDTA) is highly bioavailable.Objective To determine the effectiveness of ferric sodium edentate (NaFeEDTA) on lead levels in children woaj ;ead [pospmomg.Methods  This interventional, analytical study, had a one group pretest-posttest design, and was done on children in four elementary schools in the Talawaan District, North Minahasa Regency from August to November 2014. Inclusion criteria were elementary students aged 6-9 years with lead poisoning (lead levels ≥ 10 μg/dL) and good nutritional status. Subjects were  given NaFeEDTA 115.4 mg (15 mg elemental iron) at a dosage of 3 mg/kgBW/day elemental iron given between meal times. Iron supplementation was given daily per oral route for 12 weeks.  Descriptive analysis was used to analyze the characteristics of the study sample. Pre- and post-test analyses were done with paired T-tests. Significance level was P <0.05.Results In this study, 39 children met the inclusion criteria and consisted of 19 boys and 20 girls. Their mean age was 8.43 (SD 0.44) years. Pre-test and post-test blood lead levels was 36.18 μg/dL and 5.22 μg/dL, respectively.There was a significant reduction in mean blood lead levels after administration of NaFeEDTA (P <0.0001).Conclusion In children with lead poisoning, blood lead levels are significantly reduced after 12 weeks of NaFeEDTA supplementation.